2022
DOI: 10.14245/ns.2244604.302
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact and Correlations of Odontoid Parameters Following Multilevel Posterior Cervical Fusion Surgery

Abstract: Objective: C2 slope (C2S), a cervical parameter mathematically approximated as T1 slope minus cervical lordosis (T1S–CL), predicts functional improvement in cervical deformity patients. Nonetheless, C2S is a positional parameter based only on the horizontal axis. The current study aims to introduce novel odontoid parameters and establish their relationships with patient-reported health-related quality of life (HRQoL).Methods: Lateral plain radiographs of 32 adults who underwent multilevel posterior cervical fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Functionally, a substantial T1S necessitates a corresponding CL to achieve harmonious alignment and facilitate horizontal gaze. Insufficient CL in this context results in a high T1S–CL, adversely impacting disability scores [ 49 ]. Oe et al [ 50 ] conducted a study on 656 volunteers aged 50 to 89 years and found that cSVA> 40 mm or more, T1S> 40°, and T1S–CL> 20° had worse EuroQoL-5 dimension health status scores.…”
Section: Optimal Alignment Targets For Csd: Insights From Recent Rese...mentioning
confidence: 99%
“…Functionally, a substantial T1S necessitates a corresponding CL to achieve harmonious alignment and facilitate horizontal gaze. Insufficient CL in this context results in a high T1S–CL, adversely impacting disability scores [ 49 ]. Oe et al [ 50 ] conducted a study on 656 volunteers aged 50 to 89 years and found that cSVA> 40 mm or more, T1S> 40°, and T1S–CL> 20° had worse EuroQoL-5 dimension health status scores.…”
Section: Optimal Alignment Targets For Csd: Insights From Recent Rese...mentioning
confidence: 99%
“…Studies on the parameters for determining the level of operation segment are being investigated due to the increase in long level of segments spinal surgery, including adult spinal deformity [ 5 - 7 ]. Additionally, there is a growing interest on the complications of long level of segment spinal surgery, and the research of which materials used for wound closure might significantly reduce the length of an operation [ 8 - 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors of this article have identified alterations in the angulation of the odontoid process and in the C2 slope in cases with multisegmental cervical spondylotic myelopathy. 16 These parameters indicate alterations in alignment and spinal balance and are additional evidences that indicate atlantoaxial instability. The authors have performed spinal stabilization from C3 below.…”
mentioning
confidence: 99%
“…Craniovertebral junction has been essentially ignored in the management of degenerative spinal disease. The authors of this article have identified alterations in the angulation of the odontoid process and in the C2 slope in cases with multisegmental cervical spondylotic myelopathy [ 16 ]. These parameters indicate alterations in alignment and spinal balance and are additional evidences that indicate atlantoaxial instability.…”
mentioning
confidence: 99%